Islamic Ethics And Nutrigenomics: A Methodological Approach To Constructing A Theoretical Framework - Muhammad Fawwaz Muhammad Yusoff; Nur Izah Ab Razak; Robiatul Adawiyah Mohd @ Amat (Wise Academia Research Solutions Malaysia, 2024)
Non-Indexed Publication